IFPA meeting 2017 workshop report: Clinical placentology, 3D structure-based modeling of placental function, placental bed, and treating placental dysfunction. (April 2018) - Acharya, Ganesh; Aplin, John; Brownbill, Paul; Bulmer, Judith; Burton, Graham; Chamley, Larry; Chernyavsky, Igor; Clark, Alys; Collins, Sally; Cottrell, Elizabeth; Dilworth, Mark; Elad, David; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialized topics. At IFPA meeting 2017 there were four themed workshops, all of which are summarized in this report. These workshops discussed new knowledge and technological innovations in the following areas of research: 1) placental bed; 2) 3D structural modeling; 3) clinical placentology; 4) treatment of placental dysfunction.